Report of a new genus Majialandrevus, with a new species M. dingguo from Western Yunnan, China (Orthoptera: Gryllidae: Landrevinae) - Liu, Yi-Jiao; Xu, Jing-Yi; He, Zhu-Qing (Zootaxa, 2021)
We reported a new genus Majialandrevus from Western Yunnan, China. The new genus differs from other genera in having the following combination of characters: short forewings, male genitalia with blunt distal parts of posterolateral epiphallic lobes, absence of medial lobes of epiphallus and ectoparamere being membranous. The type specimens are deposited in the Museum of Biology, East China Normal University (ECNU).